Impact of severe haemophilia A on patients' health status: results from the guardian™ 1 clinical trial of turoctocog alfa (NovoEight®). (12th February 2015) - Ozelo, M.; Chowdary, P.; Regnault, A.; Busk, A. K.
Summary Haemophilia and its treatment interfere with patients' life and may affect adherence to treatment. This study explored the impact of severe haemophilia A on patients' health status, especially in young adults (YA), using data from guardian™ 1, a multinational, open‐label, non‐controlled phase 3 trial investigating safety and efficacy of turoctocog alfa (NovoEight®) in previously treated patients aged 12 years and older with severe haemophilia A (FVIII ≤ 1%). Health status was assessed using the EuroQoL‐5 dimensions (EQ‐5D‐3L), covering 5 dimensions of health (mobility, self‐care, usual activities, pain/discomfort and anxiety/depression), and a visual analogue scale (VAS) measuring self‐rated overall health status. EQ‐5D was administered pretreatment (screening/baseline) and posttreatment (end‐of‐trial). Baseline responses to the EQ‐5D dimensions and VAS were described overall and by age and compared to reference values from UK general population. Guardian™ 1 included 150 patients (16 adolescents, 83 YA aged 16–29 and 51 adults aged 30+). All five dimensions of patients' health status were impacted at baseline. The percentage of haemophilia patients reporting problems was consistently significantly greater than age‐matched general population reference values. Likewise, for all age groups mean baseline EQ‐5D VAS score was significantly lower for haemophilia patients (YA: 78.0) than for the general population (YA aged 18–29: 87.3). The health status of patients with severe haemophilia A entering guardian™ 1 was markedly poorer than that of the general population, particularly regarding mobility and pain. YA patients reported better health status than older patients, but considerably lower than that of the general YA population.